2018
DOI: 10.1016/j.jinf.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Improving the diagnosis of invasive aspergillosis by the detection of Aspergillus in broncho-alveolar lavage fluid: Comparison of non-culture-based assays

Abstract: The molecular detection of Aspergillus directly in BAL samples greatly improved the diagnosis of IA, particularly in non-hematological patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 44 publications
7
42
1
Order By: Relevance
“…In our cohort, the specificity of Aspergillus and panfungal PCR was similar or better to previous reports with 36%‐94% and 67%‐86% in BAL‐fluid, respectively, while their sensitivities were much lower . There are several potential explanations for the poor sensitivities of our PCR in the BAL‐fluid.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our cohort, the specificity of Aspergillus and panfungal PCR was similar or better to previous reports with 36%‐94% and 67%‐86% in BAL‐fluid, respectively, while their sensitivities were much lower . There are several potential explanations for the poor sensitivities of our PCR in the BAL‐fluid.…”
Section: Discussionsupporting
confidence: 83%
“…When test performance was re‐evaluated disregarding GM to define probable disease, sensitivity of Aspergillus and panfungal PCRs increased to 50% and 25%. This illustrates the difficulty of the diagnosis of IMD in this and many other studies . Among the 167 patients included in this study, only 6 had proven IMD.…”
Section: Discussionmentioning
confidence: 59%
“…19 Also a recent study comparing various diagnostic methods, which reported the sensitivity of MycoGenie R of 73.7% in 38 patients with proven/probable IA, had a very high (22/38, 58%) rate of positivity of culture for Aspergillus. 12 In addition, in that cohort, the sensitivity was lower in 41 hematological patients than in those from intensive care unit (ICU) suggesting a lower fungal burden sufficient to cause IFD in highly immunocompromised hosts. 12 Indeed, also the low yield of fungal cultures and rather low median BAL GM ODI confirm the low burden of viable moulds in this study.…”
Section: Discussionmentioning
confidence: 75%
“…Molecular methods such as polymerase chain reaction (PCR) are able to detect Aspergillus DNA in BAL samples with good sensitivity (77.2%) and specificity (93.5%). 10 Although in recent years many publications [11][12][13] focused on the diagnostic role of Aspergillus PCR, its use is not yet recommended in the 2016 update of IDSA Guidelines on the diagnosis and management of Aspergillosis, mostly because of the lack of standardised and validated assays. 2,3 Their advantages include the possibility to detect fungal DNA also if it is no longer viable, such as after antifungal treatment has been started, and to confirm the presence of Aspergillus with higher sensitivity than culture, similarly to GM.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of other, non‐culture‐based methods for the detection of Aspergillus has gained traction over recent years, such that current proposals for the second revision of the EORTC/MSG definitions for IMI include consideration of Aspergillus PCR assays . PCR‐based assays have a wide range of reported sensitivities and have been suggested as a way to improve diagnostic accuracy when combined with other modalities, detect azole resistance and guide judicious use of preemptive antifungal treatment . Grancini et al suggested that BAL real‐time PCR, when performed in conjunction with routine BAL culture and GM, can have a NPV of 99% in immunocompromised patients, while Hoenigl et al reported 100% sensitivity and 98% specificity when combining PCR with GM.…”
Section: Discussionmentioning
confidence: 99%